Penerapan Pembelajaran Kooperatif Tipe Think-Talk-Write Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Pada Materi Statistika di Kelas VIII SMP Parulian 1 Medan - Angela Dinaro Silalahi; W. Rajagukguk (Lembaga Pengembangan Kinerja Dosen, 2023)
Mathematics is a scientific field that investigates formless structures and forms of interaction within them. Mathematical interaction is a powerful tool used to express mathematical opinions verbally or in writing. The Think-Talk-Write (TTW) learning approach is designed to facilitate the construction, reflection, and organization of new mathematical views. This study aims to explore the efficacy of using TTW learning examples as a tactic to enhance the quality of students' mathematical communication, and to assess the impact of this approach. In order to achieve these goals, researchers used classroom action research in two stages of testing. The study involved 21 students in grade VIII at SMP Parulian 1 Medan. The initial ability test revealed that the students' mathematical communication ability scores were 34.2%. After conducting test activities in cycle I, the average mathematical communication ability of students rose to 36.8%. In the second cycle (II), the percentage result increased to 88%. The results of the research demonstrate that students in Class VIII at SMP Parulian 1 Medan experience a significant improvement in their mathematical communication skills through learning via the Think-Talk-Write model. We can conclude that this approach is an effective way to enhance students' mathematical communication skills.